Older people with swallowing dysfunction and poor oral health are at greater risk of early death. Issue 6 (13th August 2019) - Hägglund, Patricia; Koistinen, Susanne; Olai, Lena; Ståhlnacke, Katri; Wester, Per; Levring Jäghagen, Eva
Abstract: Objectives: We investigated the associations between swallowing dysfunction, poor oral health and mortality among older people in intermediate care in Sweden. Methods: This prospective cohort study investigated 391 older people in 36 intermediate care units (clusters). Swallowing function was assessed with the timed water swallow test (TWST), and oral health with the revised oral assessment guide (ROAG) at baseline. Data were collected on age, sex, education level, multimorbidity, cognitive impairment, care dependency and body mass index (BMI). Time to mortality was recorded during the following year. The mixed effects Cox regression model with cluster as a random factor was used to estimate hazards ratios (HR) with 95% confidence intervals (CI). Results: The median age of the participants was 84 years (interquartile range [IQR]: 11), and 53.3% were females. Mortality within one year was 25.1%. In the adjusted model, swallowing dysfunction and poor oral health were both independently associated with mortality (adjusted HR [aHR]: 1.67, 95% CI 1.02‐2.75; P  = .041 and aHR: 1.98, 95% CI 1.07‐3.65; P  = .029, respectively). Participants with combined swallowing dysfunction and poor oral health showed the highest mortality (35.0%) and 2.6 (95% CI 1.15‐5.89; P  = .022) times higher mortality risk than those with normal swallowing function and good oral health (13.0%). Conclusions: Swallowing dysfunction and poor oral health were identified as independent risk factors for mortality in older people in intermediate care. Although further studies are required to verify these findings, they suggest that systematic assessment of swallowing function and oral health status should be performed for care considerations.